2015
DOI: 10.1016/j.ijid.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and nephrotoxicity associated with colistin use in an intensive care unit in Vietnam: Use of colistin in a population of lower body weight

Abstract: A personalized dosing protocol of colistin was effective, with low nephrotoxicity, among critically ill Vietnamese patients with low body weight. Further studies are warranted for assessing the efficacy and toxicity in a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…Colistin-induced AKI appears to be due to the d-aminobutyric and fatty acid components of the drug, which increase cell membrane permeability resulting in cell lysis and acute tubular necrosis [6]. In the modern era, rates of AKI following colistin therapy range from 21–76% [35, 711]. Rates vary by predisposing conditions and severity of illness, but also criteria used to define AKI [6, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Colistin-induced AKI appears to be due to the d-aminobutyric and fatty acid components of the drug, which increase cell membrane permeability resulting in cell lysis and acute tubular necrosis [6]. In the modern era, rates of AKI following colistin therapy range from 21–76% [35, 711]. Rates vary by predisposing conditions and severity of illness, but also criteria used to define AKI [6, 12].…”
Section: Introductionmentioning
confidence: 99%
“…intravenous polymyxins alone in MDR GNB infections, most of which were pneumonias. It's indicated that the mortality ranged from 0% to 74.3% (4,21,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), clinical response (cure and improvement) rate 7-82.1%, and microbiological eradication 27.3-73.9% (24,(33)(34)(35)(36)(37)(38). In respect to the colistin only susceptible strains, it's reported that the mortality in hospitals of intravenous colistin monotherapy was 50% (16/32) (Figure 2), 11 patients died in Intensive Care Unit (ICU) (39), and clinical cure was obtained in 82.1% of infectious episodes (23/28) and bacteriological clearance was achieved in 73.9% (17/23) of the cured infectious episodes (38).…”
Section: Combination Therapymentioning
confidence: 99%
“…All 13 patients presented acute kidney injury, with a median of 5 days, but renal function for all cases had improvement when IV colistin was switched to inhaled colistin. Binh NG et al reported that among critically ill Vietnamese patients with low body weight, a loading dose adjusted according to total actual body weight, was associated with low nephrotoxicity (26).…”
Section: Loading Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Binh and colleagues (2015) reported a 67.9% success rate when treating patients with Colistin. However, 21.4% of the patients experienced renal damage (42). Elefritz and colleagues showed that increasing the dosage of Colistin did not increase the treatment success rate.…”
Section: Introductionmentioning
confidence: 99%